The Effect Of Use Of Audio Visual Media On Results Of Study On Social Knowledge Science In Madrasah - Siti Khoiriyah; Moh Sutomo (FALASIFA : Jurnal Studi Keislaman, 2020)
Social Sciences is an integration from various branches namely history, geography, economy, sociology and anthropology which are simplified and formulated for instructional purposes and completed with material and objectives so that they are easy to learn at the public/Islamic elementary school and public/Islamic junior high school levels. With the complexity of Social Sciences studies, effective and efficient media for learning activities are needed. So, it is very necessary for a teacher to use interesting media in the teaching and learning process. One of the interesting media can be used is audio-visual media as a means of motivating and increasing effectiveness and efficiency in achieving student learning outcomes. The purpose of this study is to examine the influence of the use of audio-visual media on student learning outcomes in social studies subjects at the Madrasah Tsanawiyah ASHRI Jember in the academic year 2019/2020. This study, used a quantitative approach with a quasi-experimental type of research, and applied a non-equivalent control group design. The population of this study was students of class VIII ASHRI Madrasah Jember. The research sample obtained through purposive sampling technique, which amounted to 74 students consisting of class VIII A as an experimental class and VIII B as a control class. Documentation in the form of post test scores was used as the data collection analysis. Analysis and test of hypotheses were done with Independent Sample T-Test and the assistance of the IBM SPSS 22.00 For Windows. By using Independent Sample T-Test as the hypothesis testing, the results of this study indicated the significance of 0,000 (2-tailed). This showed that the significance value was under 0.05, so that the null hypothesis (H0) was rejected and the alternative hypothesis (Ha) was accepted. This means that there is a significant influence on the use of audio-visual learning media on the learning outcomes of Social Sciences subject at the Madrasah Tsanawiyah ASHRI Jember in the academic year 2019/2020